PRINCIPLES FOR THE SELECTION OF THE LEXICAL UNITS FOR THE ELECTRONIC "DICTIONARY OF MYTHOLOGICAL LEXIS OF PERM REGION" (Philological Studies, 2019)
The development of the electronic “Dictionary of mythological lexis of Perm region” is the actual scientific challenge for regional lexicology and lexicography. This lexicographic product is a thematic dialect dictionary of the full type, dedicated to the Russian mythological vocabulary of the Perm region, associated with the spirits of various loci. In the article, 9 groups of the lexical items to be included in the dictionary are listed. This thematic classification of mythological vocabulary reflects the structure of the Perm tradition and serves as the basis for the development of the ideographic part of the electronic dictionary.
Keywords: electronic dictionary, mythological vocabulary, spirit of the bathhouse, brownie, wood goblin, mermaid, Perm region